Evaluating Treatment Process of Produced Water from Oil/Gas Production Platform with Scale Inhibitor - Awajiogak A, Ujile; Kenneth K, Dagde (International Journal of Chemical and Process Engineering Research, 2014)
Treatment of produced water from a crude oil production platform with a flow rate of 11,000 to 13,000 barrel per day (API 34o at 49 oC) was carried out to determine optimum concentration of the injection rate of scale inhibitor before discharge overboard. The physico-chemical properties of the produced water were determined. A GBC Scientific Avanta Programmable A6080 Atomic Absorption Spectrometer (AAS) was used to determine the cations while Analytical Method was adopted to determine the concentration of anions, conductivity, alkalinity, hardness, suspended solids, and the pH of the produced water. Results showed that conductivity, alkalinity, hardness, suspended solids decrease with increase in the concentration of the scale inhibitor. At 0 ppm of scale inhibitor, hardness was 1100 mg (CaC03) per litre of produced water and at 8.6 ppm hardness reduced to 800 mg (CaC03) per litre of produced water indicating that increasing the dosage of the scale inhibitor prevents scale formation. However, optimum dosage value is required to minimize the cost of production processes.